2014
DOI: 10.1016/j.jconrel.2013.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The systemic administration of an anti-miRNA oligonucleotide encapsulated pH-sensitive liposome results in reduced level of hepatic microRNA-122 in mice

Abstract: Efficient delivery continues to be a challenge in microRNA (miRNA) therapeutics. We utilized a pH-sensitive multifunctional envelope-type nano device (MEND) containing a pH-sensitive lipid YSK05 (YSK05-MEND) to regulate liver specific miRNA-122 (miR-122). Anti-microRNA oligonucleotides including 2'-OMe and phosphorothioate modifications against miR-122 (AMO122) were encapsulated in the YSK05-MEND. Despite the lower uptake, the YSK05-MEND showed a higher activity in liver cancer cells than Lipofectamine2000 (LF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…23 Most therapeutic applications of miRNA require packaging the nucleic acid in a vector or nanovehicle, example of which include adenovirus (AV), adeno-associated virus (AAV), liposomes, polycationic polymers, and organic/ inorganic nanoparticles. [24][25][26][27][28][29] Kota et al, for example, showed that miR-26a, a downregulated miRNA in hepatocellular carcinoma, could be delivered to liver cancer cells using AAV where it induced tumor-specific apoptosis in a mouse model of liver cancer. 30 Moreover, our group developed a poly(lactic-coglycolic acid)/polyetherimide/hyaluronan (PLGA/PEI/HA)-based vehicle as a carrier of miR-145 and further showed that PLGA/PEI/HA/miRNA complexes were delivered efficiently to tumor cells within colon carcinoma xenografts in mice where they exhibited significant antitumor effects.…”
mentioning
confidence: 99%
“…23 Most therapeutic applications of miRNA require packaging the nucleic acid in a vector or nanovehicle, example of which include adenovirus (AV), adeno-associated virus (AAV), liposomes, polycationic polymers, and organic/ inorganic nanoparticles. [24][25][26][27][28][29] Kota et al, for example, showed that miR-26a, a downregulated miRNA in hepatocellular carcinoma, could be delivered to liver cancer cells using AAV where it induced tumor-specific apoptosis in a mouse model of liver cancer. 30 Moreover, our group developed a poly(lactic-coglycolic acid)/polyetherimide/hyaluronan (PLGA/PEI/HA)-based vehicle as a carrier of miR-145 and further showed that PLGA/PEI/HA/miRNA complexes were delivered efficiently to tumor cells within colon carcinoma xenografts in mice where they exhibited significant antitumor effects.…”
mentioning
confidence: 99%
“…Detailed examinations of the physiological effects of miR-107 are needed for its safe clinical utilization. Moreover, further studies are needed on the cellular uptake or secretion systems of tumor suppressor miRNAs, leading to the development of miRNA delivery systems for future therapeutic and diagnostic applications [93][94][95][96] . These studies are currently under evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…11 In fact, the ability to control and produce a burst release of the encapsulated drug from liposomes would be extremely advantageous and may prove to be an essential step in providing effective levels of drug in the tumor. 12 Several approaches for triggered drug release from liposomes have been investigated, such as enzyme-activated, 13,14 pH-sensitive, 15,16 lightsensitive, 17,18 ultrasound-triggered, [19][20][21] and thermosensitive liposomes. [22][23][24][25][26][27][28][29][30] Thermosensitive liposomes can be prepared from phospholipids that exhibit a sharp gel-to-liquid crystalline transition.…”
Section: Introductionmentioning
confidence: 99%